2020
DOI: 10.1080/10494820.2020.1799027
|View full text |Cite
|
Sign up to set email alerts
|

Use of fitness trackers in a blended learning model to personalize fitness running lessons

Abstract: The research focuses on learning methods that address individual differences, motivation and training goals in fitness running. The aim was to examine the possibilities of use of fitness trackers in smart phones for fitness running lessons. The core of the study was to design and implement an innovative blended learning model to individualize the training process, personalize the lessons, and thus enhance students' motivation to participate. Fitness tracking applications provided quantified information about t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…Lecturers can effectively use this learning model. The results are consistent with the previous works (Calderón et al, 2021;Chaloupský et al, 2021;Priyambada et al, 2022;Syafi'i et al, 2021). The study results revealed that the model was tested using three rhythmic lecturers.…”
Section: Discussionsupporting
confidence: 93%
“…Lecturers can effectively use this learning model. The results are consistent with the previous works (Calderón et al, 2021;Chaloupský et al, 2021;Priyambada et al, 2022;Syafi'i et al, 2021). The study results revealed that the model was tested using three rhythmic lecturers.…”
Section: Discussionsupporting
confidence: 93%
“…Common modules include the student profile, generation of appropriate teaching materials, interface customization, and evaluation, and finally, (5) Cold start difficulties (n=3, f=2.9%), where some authors address the difficulty of lack of initial data from new students, for example, combining item response theory (IRT) and a trained regression tree to estimate cognitive abilities predict future student performance. Some of these studies are Chaloupský et al (2021); Kay & Kummerfeld (2019) and Lin et al (2013).…”
Section: Driver #5: Use Of Artificial Intelligence and Other Technolo...mentioning
confidence: 99%
“…Among the most popular areas for the development of educational digital mobile technologies, researchers (Aldenaini et al, 2023;Ma, 2022) pay special attention to the field of physical culture and sports, the possibility of using artificial intelligence to achieve the goals of sports education and the formation of personal qualities of athletes. This applies equally to physical education, psychological preparation of professional athletes, and amateur physical education (Chaloupský et al, 2021;Yang et al, 2020). Mobile training plans have been used previously, but the COVID-19 pandemic has amplified the use of mobile and computer applications for tracking the condition of athletes and sports students during training in both developed and developing countries (Ansari & Khan, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The use of mobile training plans in combination with tracking the fitness of athletes allows you to take into account the individual psychological characteristics of students and increase their motivation to achieve the best results (Chaloupský et al, 2021). However, despite the fact that innovative technologies improve learning, some students find it difficult to adapt to their use (Zhang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%